The Effects of Peer-Mediated Check-In/Check-Out on the Social Skills of Socially Neglected Students. (July 2016) - Collins, Tai A.; Gresham, Frank M.; Dart, Evan H.
Check-In/Check-Out (CICO) is a moderately effective Tier 2 intervention often used to address attention-maintained problem behaviors in schools. Recent studies on CICO have demonstrated the effectiveness of the intervention when combined with social skills training and when utilizing students' peers as interventionists. Using a concurrent multiple baseline across participants design, the present study evaluated the effectiveness of peer-mediated CICO to target social skills in elementary school students identified as socially neglected using a sociometric classification system. Results, implications for practice, limitations, and future directions are discussed.